Vertical structure characterization of acoustically detected zooplankton aggregation: a case study from the Ross Sea - Barra, Marco; Guglielmo, Letterio; Bonanno, Angelo; Mangoni, Olga; Rivaro, Paola; Rumolo, Paola; Falco, Pierpaolo; Basilone, Gualtiero; Fontana, Ignazio; Ferreri, Rosalia; Giacalone, Giovanni; Aronica, Salvatore; et al. (Frontiers in Marine Science, 2023)
Acoustic data were collected by means of Simrad EK60 scientific echosounder on board the research vessel “Italica” in the Ross Sea during the 2016/2017 austral summer as part of the P-Rose and CELEBeR projects, within the framework of the Italian National Research Program in Antarctica (PNRA). Sampling activities also involved the collection of vertical hydrological profiles using the SBE 9/11plus oceanographic probe. Acoustic data were processed to extract three specific scattering structures linked to Euphausia superba, Euphausia crystallorophias and the so called Sound-Scattering Layers (SSLs; continuous and low-density acoustic structures constituted by different taxa). Four different sectors of the study area were considered: two southern coastal sectors (between the Drygalski Ice Tongue and Coulman Island), a northern sector (~30 nmi East of Cape Hallett) and an offshore one spanning about 2 degrees of latitude from Coulman Island south to the Drygalski Ice Tongue. The vertical structure of each group in each area was then analyzed in relation to the observed environmental conditions. Obtained results highlighted the presence of different vertical structures (both environmental and acoustic) among areas, except for the two southern coastal sectors that were found similar. GAM modelling permitted to evidence specific relationships between the environmental factors and the vertical distribution of the considered acoustic groups, letting to hypothesize the presence of trophic relationships and differences in SSL species composition among areas. The advantages of acoustic techniques to implement opportunistic monitoring strategies in endangered ecosystems are also discussed.